Comparative genomic analysis reveals evidence of two novel Vibrio species closely related to V. cholerae - Haley, Bradd J (BioMed Central, 2010)
BACKGROUND: In recent years genome sequencing has been used to characterize new bacterial species, a method of analysis available as a result of improved methodology and reduced cost. Included in a constantly expanding list of Vibrio species are several that have been reclassified as novel members of the Vibrionaceae. The description of two putative new Vibrio species, Vibrio sp. RC341 and Vibrio sp. RC586 for which we propose the names V. metecus and V. parilis, respectively, previously characterized as non-toxigenic environmental variants of V. cholerae is presented in this study. RESULTS: Based on results of whole-genome average nucleotide identity (ANI), average amino acid identity (AAI), rpoB similarity, MLSA, and phylogenetic analysis, the new species are concluded to be phylogenetically closely related to V. cholerae and V. mimicus. Vibrio sp. RC341 and Vibrio sp. RC586 demonstrate features characteristic of V. cholerae and V. mimicus, respectively, on differential and selective media, but their genomes show a 12 to 15% divergence (88 to 85% ANI and 92 to 91% AAI) compared to the sequences of V. cholerae and V. mimicus genomes (ANI <95% and AAI <96% indicative of separate species). Vibrio sp. RC341 and Vibrio sp. RC586 share 2104 ORFs (59%) and 2058 ORFs (56%) with the published core genome of V. cholerae and 2956 (82%) and 3048 ORFs (84%) with V. mimicus MB-451, respectively. The novel species share 2926 ORFs with each other (81% Vibrio sp. RC341 and 81% Vibrio sp. RC586). Virulence-associated factors and genomic islands of V. cholerae and V. mimicus, including VSP-I and II, were found in these environmental Vibrio spp. CONCLUSIONS: Results of this analysis demonstrate these two environmental vibrios, previously characterized as variant V. cholerae strains, are new species which have evolved from ancestral lineages of the V. cholerae and V. mimicus clade. The presence of conserved integration loci for genomic islands as well as evidence of horizontal gene transfer between these two new species, V. cholerae, and V. mimicus suggests genomic islands and virulence factors are transferred between these species.